Factors Controlling the Lack of Phytoplankton Biomass in Naturally Iron Fertilized Waters Near Heard and McDonald Islands in the Southern Ocean - Wojtasiewicz, Bożena; Trull, Thomas W.; Clementson, Lesley; Davies, Diana M.; Patten, Nicole L.; Schallenberg, Christina; Hardman-Mountford, Nick J. (Frontiers in Marine Science, 2019)
The Kerguelen Plateau is one of the regions in the Southern Ocean where spatially large algal blooms occur annually due to natural iron fertilization. The analysis of ocean colour data as well as in situ samples collected during the Heard Earth-Ocean-Biosphere Interactions (HEOBI) voyage in January and February 2016, surprisingly revealed that chlorophyll a concentrations in waters located close to Heard and McDonald islands were much lower than those on the central Kerguelen Plateau. This occurs despite high levels of both glacial and volcanic iron supply from these islands. The analysis of pigment and optical data also indicated a shift in the phytoplankton size structure in this region, from a microphytoplankton to nanophytoplankton dominated community. Possible explanations for this high nutrient, high iron (Fe), low chlorophyll (HNHFeLC) phenomenon were explored. Low light availability due to deep mixing and shading by re-suspended sediment particles and augmented by dilution with surrounding low chlorophyll waters in the Antarctic Circumpolar Current was shown to be an important mechanism shaping phytoplankton communities. The competing dynamics between stimulation and limitation illustrate the complexity of short-term responses to our changing climate and cryosphere.